1992
DOI: 10.1002/pola.1992.080300609
|View full text |Cite
|
Sign up to set email alerts
|

Soluble polyarylenes containing alternating binaphthylene and biphenylene structural units

Abstract: This article describes the synthesis of a novel series of soluble polyarylenes containing alternating binapthylene and biphenylene structural units. They were obtained by the cation‐radical polymerization of bis(1‐naphthyl) biphenyls. The following monomers were synthesized and polymerized : 4,4′‐bis(1‐naphthyl) biphenyl (9), 3,3′‐bis(1‐naphthyl) biphenyl (10), 2,2′‐bis(1‐naphthyl)biphenyl (11), and 2,5‐bis(1‐naphthyl)biphenyl (14). All polymerizations were performed in nitrobenzene using FeCl3 as oxidant. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Hückel molecular orbital calculations performed using another azomethine monomer containing a 1-substituted naphthalene group, that is N-pyrrolylmethylene-1-aminonaphthalene, have shown that the most probable polymer structure results from participation of the naphthalene group by its 4-position and the pyrrole ring by its a-posi- tion. [34] Also, chemical polymerization (FeCl 3 as oxidant) of bis(1-naphthoxy)aryls [35] and bis(1-naphthyl)aryl [36] monomers led to polymer structures containing a naphthalene group as a 1,4-disubstituted ring. The major feature of the synthesized polyazomethines is their good solubility in aprotic organic solvents (DMSO, DMF, DMAc) unlike most aromatic poly(Schiff base)s which are insoluble.…”
Section: Resultsmentioning
confidence: 99%
“…Hückel molecular orbital calculations performed using another azomethine monomer containing a 1-substituted naphthalene group, that is N-pyrrolylmethylene-1-aminonaphthalene, have shown that the most probable polymer structure results from participation of the naphthalene group by its 4-position and the pyrrole ring by its a-posi- tion. [34] Also, chemical polymerization (FeCl 3 as oxidant) of bis(1-naphthoxy)aryls [35] and bis(1-naphthyl)aryl [36] monomers led to polymer structures containing a naphthalene group as a 1,4-disubstituted ring. The major feature of the synthesized polyazomethines is their good solubility in aprotic organic solvents (DMSO, DMF, DMAc) unlike most aromatic poly(Schiff base)s which are insoluble.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerization of u,u>-bis( 1-naphth0xy)alkanes under Scholl reaction conditions led to the synthesis of polyethers with both aromatic and aliphatic segments (20,21). The synthesis of soluble aromatic polyethers by Scholl reaction was achieved in our laboratory only recently (22)(23)(24)(25)(26).…”
Section: Single-electron Transfermentioning
confidence: 99%
“…The cation-radical polymerization of bis(1-naphthoxy) substituted monomers is presented in eq 26. The central units of the monomers are summarized in Table 2.…”
Section: Cation-radical Dolvmerization Of Bis(l-nauhthoxv) S W T U T mentioning
confidence: 99%
See 1 more Smart Citation
“…Percec et al carried out pioneering work in the field of molecular engineering of main chain and side chain liquid crystalline polymers. In most of their liquid crystal molecular engineering studies, 1-(4hydroxyphenyl)-2-(2-methyl-4-hydroxyphenyl) ethane was employed as mesogen (based on conformational isomerism) in the main chain polymers [48][49][50][51][52][53][54][55][56][57] and biphenyl based structures were employed as mesogens in side chain polymers. [58][59][60][61][62][63][64][65][66][67] They investigated the tolerated limits of flexibility of nematic state in polyethers not only by introducing flexible spacers but also by the degree of flexibility provided by the mesogen.…”
Section: Introductionmentioning
confidence: 99%